Compounding impact of severe weather events fuels marine heatwave in the coastal ocean - B. Dzwonkowski (Nature Portfolio, 2020)
Exposure to extreme events is a major concern in coastal regions where human populations and stressed ecosystems are at risk to such phenomena. Here the authors show a marine heatwave on the continental shelf resulted from a novel set of compounding effects due to a tropical storm followed by an atmospheric heatwave.